The politics of women's rights in Iran - Osanloo, Arzoo, 1968- (Anthropology online., 2009)
"In The Politics of Women's Rights in Iran, Arzoo Osanloo explores how Iranian women understand their rights. After the 1979 revolution, Iranian leaders transformed the state into an Islamic republic. At that time, the country's leaders used a renewed discourse of women's rights to symbolize a shift away from the excesses of Western liberalism. Osanloo reveals that the postrevolutionary republic blended practices of a liberal republic with Islamic principles of equality. Her ethnographic study illustrates how women's claims of rights emerge from a hybrid discourse that draws on both liberal ndividualism and Islamic ideals. Osanloo takes the reader on a journey through numerous sites where rights are being produced--including Qur'anic reading groups, Tehran's family court, and law offices--as she sheds light on the fluid and constructed nature of women's perceptions of rights. In doing so, Osanloo unravels simplistic dichotomies between so-called liberal, universal rights and insular, local culture. The Politics of Women's Rights in Iran casts light on a contemporary non-Western understanding of the meaning behind liberal rights, and raises questions about the misunderstood relationship between modernity and Islam"--Provided by publisher